A Novel Formulation of Fosamprenavir Calcium: Therapeutic Deep Eutectic Solvent with Enhanced Properties - Jasna Prlić Kardum; Iva Zokić; Aleksandra Sander; Patricija Pelin (Crystals)
In the pharmaceutical industry, deep eutectic solvents can be used to enhance the solubility, permeability, and absorption of active pharmaceutical ingredients. In this paper, deep eutectic solvents were prepared by combining the active pharmaceutical ingredient fosamprenavir calcium with lactic acid in certain molar ratios. The aim of this study was to create a therapeutic deep eutectic solvent with the same therapeutic effect as the active pharmaceutical ingredient, but with enhanced properties. 1H NMR and FTIR spectroscopy were used to identify and characterize the chemical composition and structural changes of the prepared THEDES. Maximum solubility, the release of the active pharmaceutical ingredient from the therapeutic deep eutectic solvent, and permeability were tested. Different mathematical models were chosen to describe the kinetic behavior of the drug release.